Fisiologia da termorregulação e estresse térmico em ovinos lanados - Matsukuma, Bruno Henrique [UNESP]; Peiró, Juliana Regina [UNESP]; Feitosa, Francisco Leydson Formiga [UNESP]; Mendes, Luiz Claudio Nogueira [UNESP] (My University, 2010)
The introduction of wool sheep in warm temperature regions of Brazil has also raised concerns regarding the warm stress and its consequent decrease in animal production. The understanding of the physiology of thermal balance in sheep, as well as the consequences of this phenomenon, should be studied in order to improve animal thermal comfort in association with the production and reproduction indices of these animals. The majority of available research findings related to thermal balance in sheep is derived from countries with temperate climates and therefore might be different from those performed in our climate conditions. This essay presents a literature review that intends to discuss this theme.

O ingresso dos ovinos lanados em regiões quentes do Brasil trouxe também a preocupação com o estresse calórico e consequente queda na produção animal. A compreensão da fisiologia do equilíbro térmico ovino, assim como as consequências desse fenômeno, devem ser estudadas a fim de promover um conforto térmico associado aos índices de produção e reprodução destes animais. Os casos estudados sobre o assunto são em sua maioria oriundos de países com clima temperado e, por isso, os resultados podem ou não apresentar semelhança. Esta revisão de literatura apresenta e discute o tema.
Thermal balance physiology and heat stress in wool sheep
Keywords: Sheep; Shearing; Heat stress; Ovinos; Tosquia; Estresse térmico